Some Infinite Sums Related to the \(k\)-Fibonacci Numbers - Karaoğlu, Onur; Uslu, Kemal (Communications in Mathematics and Applications, 2018)
In this study, some infinite sums related to the \(k\)-Fibonacci numbers have been obtained by using in…nite sums related to classic Fibonacci numbers in literature.